Development of an Early, High-Yield, Promising Variety of Chinese cabbage (Brassica Rapa Subsp. Chinensis L) - Khurramovna, Khudoyorova Hafiza (American Journal of Botany and Bioengineering, 2024)
Chinese cabbage is a non-traditional vegetable crop for Uzbekistan, in order to expand the assortment of vegetable crops in the climate of our Republic Chinese cabbage introduced from abroad, inclTaiwan, Chinaand belongs to the Russian states 13 variety samples were studied for morpho-biological and valuable economic characters andAs a model variety, the regionalized "Eastern Beauty" variety, regionalized in Uzbekistan, was taken. As a result of three years of research, 3 early and 3 primary sources were selected according to the sign of yield.